Faith, family, and Filipino American community life - Cherry, Stephen M. (Rutgers University Press, 2014)
This ground-breaking book draws upon a rich set of ethnographic and survey data, collected over a six-year period, to explore the roles that Catholicism and family play in shaping Filipino American community life. It illustrates the powerful ways these forces structure and animate not only how first-generation Filipino Americans think and feel about their community, but how they are compelled to engage it over issues deemed important to the sanctity of the family.